2019
DOI: 10.1038/s41551-019-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap for the clinical implementation of optical-imaging biomarkers

Abstract: Clinical workflows for the non-invasive detection and characterization of disease states could benefit from optical-imaging biomarkers. In this Perspective, we discuss opportunities and challenges towards the clinical implementation of optical-imaging biomarkers for the early detection of cancer by analysing two case studies: the assessment of skin lesions in primary care, and the surveillance of patients with Barrett's oesophagus in specialist care. We stress the importance of technical and biological validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 192 publications
(206 reference statements)
0
64
0
Order By: Relevance
“…Machine (ML) and deep learning (DL) algorithms are used to automatically extract and analyze histogram, texture, and shape information from imaging data which may not be evident to the naked eye. Given the limitations of conventional medical imaging, there is increased interest to apply radiomics in oncological imaging as a tool to obtain diagnostic, predictive, and prognostic information from routine clinical imaging [16]. However, despite its extensive use in research and favorable results linking CT/MRI texture features to renal mass characterization, the routine use of radiomics in clinical practice is yet to be seen.…”
Section: Renal Mass Differentiationmentioning
confidence: 99%
“…Machine (ML) and deep learning (DL) algorithms are used to automatically extract and analyze histogram, texture, and shape information from imaging data which may not be evident to the naked eye. Given the limitations of conventional medical imaging, there is increased interest to apply radiomics in oncological imaging as a tool to obtain diagnostic, predictive, and prognostic information from routine clinical imaging [16]. However, despite its extensive use in research and favorable results linking CT/MRI texture features to renal mass characterization, the routine use of radiomics in clinical practice is yet to be seen.…”
Section: Renal Mass Differentiationmentioning
confidence: 99%
“…The studies reviewed here indicate that PAI can inform on TME features in preclinical models and holds promise for clinical translation. Currently, further technical and biological validation of PAI biomarkers is needed to increase uptake of the modality in studies of TME biology or clinical evaluation of TME features (Waterhouse et al, 2019). In terms of technical validation, some studies have reported on standardisation of data acquisition and analysis (Abeyakoon et al, 2018; Bohndiek et al, 2013; Joseph et al, 2017; Martinho Costa et al, 2018; Neuschmelting et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, scouting for pathological features may help guide and expedite 323 histopathological follow-up studies. Thirdly, digitized 3D image libraries of tissue and organs from 324 TB patients could be used to identify novel imaging biomarkers based on patterns of differential 325 radio-opacities 42 (Table 1). 347 348…”
Section: Tb Lesion Formation Through Bronchial Obstruction 203mentioning
confidence: 99%